Studies of parametric emissions monitoring and DLN combustion NOx formation - Keller, Ryan A. (Kansas State University, 2011)
The increased emissions monitoring requirements of industrial gas turbines have created a demand for less expensive emissions monitoring systems. Typically, emissions monitoring is performed with a Continuous Emissions Monitoring System (CEMS), which monitors emissions by direct sampling of the exhaust gas. An alternative to a CEMS is a system which predicts emissions using easily measured operating parameters. This system is referred to as a Parametric Emissions Monitoring System (PEMS). A review of the literature indicates there is no globally applicable PEMS. Because of this, a PEMS that is applicable to a variety of gas turbine manufacturers and models is desired. The research presented herein includes a literature review of NOx reduction techniques, NOx production mechanisms, current PEMS research, and combustor modeling. Based on this preliminary research, a combustor model based on first-engineering principles was developed to describe the NOx formation process and relate NOx emissions to combustion turbine operating parameters. A review of available literature indicates that lean-premixed combustion is the most widely-used NOx reduction design strategy, so the model is based on this type of combustion system. A review of the NOx formation processes revealed four well-recognized NOx formation mechanisms: the Zeldovich, prompt, nitrous oxide, and fuel-bound nitrogen mechanisms. In lean-premixed combustion, the Zeldovich and nitrous oxide mechanisms dominate the NOx formation. This research focuses on combustion modeling including the Zeldovich mechanism for NOx formation. The combustor model is based on the Siemens SGT-200 combustion turbine and consists of a series of well-stirred reactors. Results show that the calculated NOx is on the same order of magnitude, but less than the NOx measured in field tests. These results are expected because the NOx calculation was based only on the Zeldovich mechanism, and the literature shows that significant NOx is formed through the nitrous oxide mechanism. The model also shows appropriate trends of NOx with respect to various operating parameters including equivalence ratio, ambient temperature, humidity, and atmospheric pressure. Model refinements are suggested with the ultimate goal being integration of the model into a PEMS.
Keywords: PEMS; Combustion; Gas turbine; NOx; Lean premixed; DLN; Chemical Engineering (0542); Mechanical Engineering (0548)